The relationship of self-control and authoritative parenting patterns with smoking behavior in vocational adolescents in Gowa Regency - Harma, Asmarani; Hardi, Hardi; Latief, Mutmainnah (Gema Wiralodra, 2023)
A hostile sociocultural environment is one of the risk factors for adolescents engaging in unhealthy behaviors, one of which is smoking. Smoking behavior is a growing problem that has not yet been solved in Indonesia. The implementation of various policies and strict regulations regarding cigarettes should reduce smoking behavior among adolescents, but the reality is not so and tends to be the opposite. Adolescents ' attitudes are greatly influenced by their self-concept, and one form of positive self-concept is self-control. On the other hand, families with an authoritative parenting style are the primary environment that influences various aspects of a person's development, including the development of teenagers. The purpose of this study is to determine the relationship between self-control and smoking behavior among vocational high school students in Gowa Regency and the relationship between authoritative parenting style and smoking behavior among vocational high school students in Gowa Regency. The research design used a cross-sectional study approach with a purposive random sampling method. The results of the study show that there is a significant relationship between self-control and smoking behavior and a significant relationship between authoritative parenting style and smoking behavior among vocational high school students in Gowa Regency.